Anaplastic lymphoma kinase inhibitors. (August 2015) - Crescenzo, Ramona; Inghirami, Giorgio
Graphical abstract: ALK signaling: Wild type (WT) ALK receptor (ALKr) requires ligand dimerization to trigger cellular signaling, conversely mutated ALKr and over expressed WT ALKr can efficiently signal even in presence of ligands. ALK fusions are ligand independent. ALK inhibitors (ALKi) block the ATP binding pocket (depicted as a blue oval). Mutation-driven resistant mechanisms can be overcome by second-generation compounds. A representation of the apo-crystal structure of ALK (shown in the low right side of the panel, (http://www.rcsb.org/pdb/explore/explore.do?structureId=3L9P). Highlights: ALK inhibitors (ALKi) are effective compounds in molecularly stratified human cancers. Second generation of ALKi are currently being tested in ALKi-resistant neoplasms. 'Dirty' ALKi may limit the occurrence of ALKi resistant phenotypes. The combination of ALKi with immune-based antagonists may improve responses. Abstract : The anaplastic lymphoma kinase (ALK) gene is a member of the insulin receptor superfamily and it has been associated with more than twenty distinct chimera, including established drivers of several human cancers. Multiple clinical trials have proven that the pharmacological inhibition of ALK signaling leads to remarkable clinical improvement and improves the quality of life of ALK+ cancer patients. Crizotinib was the first ALKi to achieve approval from the Food and Drug Administration, although additional compounds are now moving into diversified clinical trials.